Poetics of Space in the Novel of Yurii Yanovskyi Master of the Ship - Shteinbuk, Feliks (Poznańskie Studia Slawistyczne, 2024)
The article is the analysis of the spatial organization of Yurii Yanovskyi’s novel Master of the Ship. Using the hermeneutic and comparative-typological method, the author concludes that space dominates in this literary work, as opposed to time. The space is formed by synthesizing the topoi of the sea and the steppe; it is characterized by a heterogeneous structure consisting of the space of death, corporeality, culture, social, and others. These spaces interact with one another both on the basis of consonance and contradiction. The space of the novel substantially substantiates its ideological and artistic content, which can be defined as the author’s contradictory attempt to establish the emergence of a new “beautiful” world.